Aluminum Exposure Induces Time-Dependent Cognitive Decline, Anxiety, and Brain Aluminum Accumulation in Rats - Amirul Hafiz Ahmad Abdullah; Husna Anuar; Nur Afiqha Rosli; Hilal Haiqal Faizal; Kalaimathy Moothy; Muhammad Hafiz Zuhdi Fairof; Nurul Farhana Jufri; Siti Fathiah Masre; Nor Fadilah Rajab; Farah Wahida Ibrahim (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Aluminum, a nonessential element, can accumulate in the brain and has been implicated in neurodegenerative disorders such as Alzheimer’s disease (AD). Although previous studies have examined aluminum neurotoxicity, many focus on a single time point, limiting insight into how aluminum accumulates over time. This study addresses that gap by investigating time-dependent aluminum accumulation and associated neurobehavioral changes in rats at 14, 28, and 42 days.METHODS: Male Wistar rats were administered 200 mg/kg/day aluminum chloride (AlCl3) via oral gavage for 14 (acute), 28 (subacute), and 42 (subchronic) days. Cognitive and anxiety-like behaviors were assessed using the 2-novel object recognition (2NOR) test, spontaneous alternation Y-maze, and open field test (OFT). Brain aluminum levels were quantified using inductively coupled plasma mass spectrometry (ICP-MS).RESULTS: There were impairments in spatial and non-spatial memory and increased anxiety-like behavior across all exposure durations (p<0.05). Non-spatial memory performance decreased by 50.5%, 37.7%, and 56.2% on day-14, -28, and -42, respectively. Spatial memory significantly declined by 34.3% and 43.2% on day-14 and -42, respectively, while the 20.0% decrease at day-28 was not statistically significant. Anxiety-like behavior increased, with center zone entries reduced by 37.6%, 64.9%, and 62.9% across the same time points. Brain aluminum concentrations were significantly elevated in all aluminum-exposed groups compared to controls, with increases of 2,622.6%, 314.7%, and 969.3% on day-14, -28, and -42, respectively (p<0.05). The increase was not strictly proportional to exposure duration, suggesting possible homeostatic regulation. Weight and liver assessments confirmed the subtoxic nature of the exposure.CONCLUSION: Exposure to aluminum for 42 days induces behavioral deficits and increases brain aluminum levels, which may support its potential relevance as a model to study aluminum-induced neurotoxicity.KEYWORDS: aluminum exposure, cognitive function, anxiety, temporal progression, neurobehavioral changes